Quantitative Proteome Profiling of Coxiella burnetii Reveals Major Metabolic and Stress Differences Under Axenic and Cell Culture Cultivation - Dresler, Jiri; Klimentova, Jana; Pajer, Petr; Salovska, Barbora; Fucikova, Alena Myslivcova; Chmel, Martin; Schmoock, Gernot; Neubauer, Heinrich; Mertens-Scholz, Katja (Frontiers in Microbiology, 2019)
Coxiella burnetii is the causative agent of the zoonotic disease Q fever. To date, the lipopolysaccharide (LPS) is the only defined and characterized virulence determinant of C. burnetii. In this study, proteome profiles of C. burnetii Nine Mile phase I (RSA 493, NMI) and its isogenic Nine Mile phase II (RSA 439 NMII) isolate with a deep rough LPS were compared on L-929 mouse fibroblasts and in complex (ACCM-2) and defined (ACCM-D) media. Whole proteome extracts were analysed using a label free quantification approach. Between 659 and 1046 C. burnetii proteins of the 2132 annotated coding sequences (CDS) were identified in any particular experiment. Proteome profiles clustered according to the cultivation conditions used, indicating different regulation patterns. NMI proteome profiles compared to NMII in ACCM-D indicate transition from exponential to stationary phase. The levels of regulatory protein such as RpoS, CsrA2, UspA1 and UspA2 were increased. Comparison of the oxidative stress response of NMI and NMII indicated that ACCM-2 represents a high oxidative stress environment. High expression of peroxidases, superoxide dismutases as well as thioredoxins was observed for NMI. Contrary, in ACCM-D only osmoregulation seems to be necessary. Proteome profiles of NMII do not differ and indicate that both axenic media represent similar oxidative stress environments. Deep rough LPS causes changes of the outer membrane stability and fluidity. This might be one reason for the observed differences. Proteins associated with the T4SS and Sec translocon as well as several effector proteins were detectable under all three conditions. Interestingly, none of these putatively secreted proteins are upregulated in ACCM-2 compared to ACCM-D and L-929 mouse fibroblasts. Curiously, a higher similarity of proteomic patterns (overlapping up- and down regulated proteins) of ACCM-D and bacteria grown in cell culture was observed. Particularly, the proteins involved in the better adaptation or homeostasis in response to the harsh environment of the parasitophorous vacuole were demonstrated for NMI. This semi-quantitative proteomic analysis of C. burnetii compared axenically grown bacteria to those propagated in cell culture.